A Comparison of Left Dislocation Constructions in Biblical Hebrew and Sesotho: Implications for Pedagogy and Linguistic Typology - Makutoane, Tshokolo; Motsei, Anastacia (Journal for Semitics, 2025)
African students are taught the grammar of Biblical Hebrew (BH) from the perspective of Western languages, even though African languages have some features closer to BH than Western ones. It is observed that African students, especially those who speak Sesotho, find it challenging to understand and translate left dislocation in BH. The development of scholars’ understanding of this construction has led to confusion between left dislocation and topicalisation. This article intends to address these problems to provide students with an understanding of left dislocation and topicalisation in Sesotho by comparing the Sesotho constructions with those in BH. This endeavour supports an overarching strategy of South African universities to decolonise the curriculum. The theoretical framework on which this study is based is linguistic typology, which is a field of linguistics that studies and classifies languages according to their structural features to allow multiple comparisons of the cross-linguistic data. By recognising the similarities and differences between Sesotho and BH, Sesotho students will better understand BH left dislocation. In comparing and contrasting these two languages, we will critically examine the Sesotho Bible translation of 1909, revised in 1961, and the translation of 1989(R), which is currently under revision.